Phytochemical and antioxidant composition of crude water extracts of Chlorella vulgaris and its effects on Saccharomyces cerevisiae growth in an ethanolic medium - Queency N. Okechukwu (Техника и технология пищевых производств)
Chlorella vulgaris is rich in secondary metabolites that defend against environmental stress and aid in detoxification. In particular, bioactive compounds extracted from C. vulgaris may enhance the growth of microorganisms and detoxify them in an ethanolic medium. We aimed to effectively extract and characterize bioactive compounds found in C. vulgaris and further test them for their beneficial effects on the growth of Saccharomyces cerevisiae cultured in an ethanolic medium. Bioactive compounds in C. vulgaris were extracted using ultrasound and water as solvents. The extracts were analyzed for total phenol and flavonoid contents as part of their phytochemical composition. Their DPPH radical activity and Hydrogen peroxide scavenging activity were examined to determine their antioxidant properties and protective potential for S. cerevisiae in an ethanolic medium. Further, the extracts were added at 0.1, 0.5, 1, 2, 3, and 4% w/v concentrations into S. cerevisiae culture induced with 1% v/v ethanol for 23 days. The yeast cells’ density and viability were measured after 2, 5, 9, 13, 17, and 23 days. The extracts of C. vulgaris were rich in phenols and flavonoids, which are important bioactive compounds. Higher concentrations of the extracts increased total phenols up to 47.67 GAE mg/L and total flavonoids up to 218.67 QE mg/L. The extracts’ antioxidant composition showed high DPPH activity (70.12%) and H2O2 scavenging activity (4.97%). After 23 days, the samples treated with C. vulgaris extracts maintained a high viability of the yeast cells. In particular, the samples with 2, 4, 0.1, and 1% of the extract had a cell viability of 95.75, 94.04, 89.15, and 74%, respectively. The positive control (1% ethanol alone) and negative control (yeast alone) had 47.71 and 21.01% viability, respectively. This drastic reduction in viability was due to lysis of the yeast cells caused by ethanol. Ultrasound extraction with water as a solvent produced abundant beneficial secondary metabolites from C. vulgaris. The addition of C. vulgaris extract increased the viability and cell density of S. cerevisiae after 27 days, thereby protecting the yeast cells from the toxic effects of ethanol.